The effect of thyroid disorders on the cutaneous manifestations in patients with chronic kidney disease - Zewei Chen; Weifeng Hu; Erwen Kou; Bo Wang; Yuanjie Zhu; Nanmei Liu (Renal Failure)
For several decades, the cutaneous manifestations related to chronic kidney disease (CKD) have presented substantial clinical challenges. However, the underlying etiology and pathophysiology of these manifestations remain incompletely understood. Thyroid disorders represent a highly prevalent but often under-recognized endocrine dysfunction in patients with CKD. Recently, several studies have suggested that thyroid disorders play critical roles in modulating the cutaneous manifestations related to CKD and serve as a key factor in effectively addressing these issues. However, there is a notable lack of systematic reviews that comprehensively summarize the effect of thyroid disorders on CKD-related cutaneous manifestations, thereby impeding the advancement of research in this domain. In this review, we summarized the current knowledge on the effect of thyroid disorders on cutaneous manifestations related to CKD. Then, the underlying mechanisms through which thyroid disorders may induce or aggravate these cutaneous manifestations were further discussed. This comprehensive analysis can enhance our understanding on the roles of thyroid disorders in dermatological complications related to CKD, and help to identify novel targets and strategies for the effective management toward these refractory cutaneous manifestations.